Carbon nanomaterials for drug delivery and tissue engineering - Shaolie Zheng; Yuan Tian; Jiang Ouyang; Yuan Shen; Xiaoyu Wang; Jian Luan (Frontiers in Chemistry, 2022)
Carbon nanomaterials are some of the state-of-the-art materials used in drug-delivery and tissue-engineering research. Compared with traditional materials, carbon nanomaterials have the advantages of large specific surface areas and unique properties and are more suitable for use in drug delivery and tissue engineering after modification. Their characteristics, such as high drug loading and tissue loading, good biocompatibility, good targeting and long duration of action, indicate their great development potential for biomedical applications. In this paper, the synthesis and application of carbon dots (CDs), carbon nanotubes (CNTs) and graphene in drug delivery and tissue engineering are reviewed in detail. In this review, we discuss the current research focus and existing problems of carbon nanomaterials in order to provide a reference for the safe and effective application of carbon nanomaterials in drug delivery and tissue engineering.